Implementation of Follow-up Actions on the Results of Inspectorate Audits in Central Maluku Regency - Umiasalamu Tuasikal; Normawati Normawati; Wahab Tuanaya; Safrudin Bustam Layn (Journal of Government Science Studies, 2025)
Internal oversight is an important instrument in ensuring accountability and transparency in regional government administration. The Regional Inspectorate, as the Government Internal Oversight Agency (APIP), has a strategic role in overseeing the effectiveness of governance, particularly through follow-up on audit results. This study aims to analyse the implementation of follow-up actions on audit findings by the Inspectorate in Central Maluku Regency and to identify the determining factors that influence it. Using a qualitative approach, data was collected through interviews, documentation, and observation, and then analysed descriptively. .The results of the study show that although the regulatory framework is in place, the implementation of follow-up recommendations has not been optimal. The average follow-up completion rate in Central Maluku Regency is 70-75 per cent, with variations between OPDs. Some OPDs have shown a good response, but others are still below 60 per cent. The implementation of TLHP still faces obstacles in the form of differences in compliance levels between OPDs, which are influenced by the weak commitment of some OPD leaders, limited resources, a lack of technical understanding, and the minimal application of sanctions, where the quality of follow-up is still largely administrative in nature. Factors influencing this achievement include Human Resource Capacity, Internal Administration and Management Systems, Commitment of OPD Leaders, and Sanctions and Rewards (Incentives). These conditions emphasise the importance of strengthening the capacity of the Inspectorate, proactive leadership, and the use of information systems to ensure higher quality and more targeted follow-up, as well as the application of sanctions and rewards, thereby improving the overall accountability and performance of local government. This study confirms that the effectiveness of oversight is not only determined by the quality of audits, but also by political will, organisational culture, and the sustainability of monitoring mechanisms. Therefore, it is necessary to strengthen the capacity of the Inspectorate, apply strict sanctions, and foster a culture of accountability to encourage improvements in local government governance.